Ars metabolica Stoffwechsel und Digestion als literarische und kulturelle Prozesse - Höving, Vanessa; Risthaus, Peter (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Metabolic and digestive concepts shape how we speak about literature and reading. It is a matter of 'digesting' the material and 'letting it sink in' or letting remarkable passages 'melt in one's mouth'. Fictional as well as non-fictional texts virtually labour on the knowledge of food, metabolism and digestion and their cultural semiotic implications. Under the heading of 'Ars metabolica', this book examines depictions of consumption and dietetics, transformation and utilisation, and circulation and excretion. It becomes apparent that digestion and metabolism are far more than metaphors and that culture must be thought of in terms of their respective residues. Historically, the articles in this study address topics from the Enlightenment to contemporary literature.